Facet‐Resolved Electrochemistry of Polycrystalline Boron‐Doped Diamond Electrodes: Microscopic Factors Determining the Solvent Window in Aqueous Potassium Chloride Solutions. Issue 20 (6th August 2018) - Liu, Dan‐Qing; Chen, Chang‐Hui; Perry, David; West, Geoff; Cobb, Sam J.; Macpherson, Julie V.; Unwin, Patrick R.
Abstract: A systematic examination of the microscopic factors affecting the aqueous solvent (electrolyte) window of polycrystalline (p) boron‐doped diamond (BDD) electrodes in chloride‐containing salt solutions is undertaken by using scanning electrochemical cell microscopy (SECCM) in conjunction with electron backscatter diffraction (EBSD) and Raman microscopy. A major focus is to determine the effect of the local boron doping level, within the same orientation grains, on the solvent window response. EBSD is used to select the predominant (110) orientated areas of the surface with different boron‐doped facets, thereby eliminating crystallographic effects from the electrochemical response. Voltammetric SECCM is employed, whereby a cyclic voltammogram is recorded at each pixel mapped by the meniscus‐contact SECCM cell. The data obtained can be played as an electrochemical movie of potential‐resolved current maps of the surface to reveal spatial variations of electroactivity, over a wide potential range, including the solvent (electrolyte) window. Local heterogeneities are observed, indicating that the solvent window is mainly linked to local dopant levels, with lower dopant levels leading to a wider window, that is, slower electrode kinetics for solvent/electrolyte electrolysis. Furthermore, the effects of O‐ and H‐surface termination of the BDD surface are investigated for the same electrode (in the same area). The surface termination is a particularly important factor: the solvent window of an H‐terminated surface is wider than for O‐termination for similar boron dopant levels. Furthermore, the anodic potential window of the O‐terminated surface is greatly diminished due to chloride electro‐oxidation. These studies provide new perspectives on the local electrochemical properties of BDD and highlight the importance of probing the electrochemistry of BDD at the level of a single crystalline grain (facet) to unravel the factors that control the solvent (aqueous) window of these complex heterogeneous electrodes. Abstract : Factors affecting solvent window : The boron doping level and surface termination are important for changing the solvent window of boron‐doped diamond (BDD), as illustrated by correlative electrochemical microscopy (see picture).